(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The use of technology has developed into an integral part of human life in today’s world. Financial technological services have become a key driver of financial inclusion in the country. This study aims to examine the impact of various key factors on the enhancement of financial inclusion through FinTech services. Methods: This study incorporated positivist philosophy, a descriptive and causal research design was considered and a survey was conducted among 200 bank customers in Gandaki province in Nepal. Proposed hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) and descriptive results were analyzed using SPSS-26. Results: The result shows that the behavioural intention, social trust and usability had a significant positive impact on financial inclusion. The Social influence does not show a significant impact on it. Results and findings indicate that the importance of customer motivation, trust in digital platforms and user-friendly technological applications promote inclusive financial involvement. Conclusions: In the developing economies, digital transformation is essential to promote an inclusive financial system. The willingness to adopt technology, which is trustworthy and user-friendly are promotes an inclusive and impartial financial system. This study contributes to the literature on the incorporation of FinTech services in banks and financial institutions, as well as policy formulation to design user-centred and trustworthy digital financial services.